Medicinal Chemistry for Sustainable Development - da S.M. Forezi, Luana; Ferreira, Patricia G.; de Carvalho, Alcione S.; de C. da Silva, Fernando; Ferreira, Vitor F. (Current Topics in Medicinal Chemistry, 2023)
Pharmaceutical chemistry has many industrial processes that must be studied and adapted to a new reality where the environment must be the focus of all production chains. Thus, new technologies that are cleaner and use renewable sources of raw materials still need to be developed and applied to materials that go to the market, and they need to reach a level that is less harmful to the environment. This applies especially in areas related to the pharmaceutical industries since chemical products are used in the production of medicines and used in many other areas of everyday life and are included in the Sustainable Development Goals proposed by the United Nations. This article intends to provide insight into some relevant topics that can stimulate researchers toward medicinal chemistry that can contribute to a sustainable future of the biosphere. This article is structured around four interconnected themes that influence how green chemistry can be important for a future where science, technology and innovation are key to mitigating climate change and increasing global sustainability.
Keywords: Green chemistry